THE MEDIATING & MODERATING EFFECT OF WORK MOTIVATION IN THE RELATIONSHIP BETWEEN WORK ETHICS AND EMPLOYEE PERFORMANCE - Ari Luthfi, Muhammad; Nur Fu’ad, Eko (Distribusi - Journal of Management and Business, 2025)
This research seeks to examine how work ethics influence employee performance, as well as the impact of work motivation in both mediating and moderating this relationship. The sample for this research consisted of 170 employees at CV. ABC within the production division. The selection of the research sample was conducted using the Slovin formula, resulting in 75 respondents chosen through a random sampling method. Data was gathered through a questionnaire employing a Likert scale, and the analysis was completed using SmartPLS 4.0. The findings indicated that both work ethics and work motivation have a significant effect on employee performance, and work motivation serves as a mediator and moderator in the connection between work ethics and performance. The study offers suggestions for CV. ABC’s management to bolster work ethics. Furthermore, businesses should focus on elevating employee motivation through recognition, incentives, and rewards to foster a productive and cohesive workplace. From a theoretical standpoint, this research broadens the application of Social Exchange theory by illustrating the dual functionality of work motivation as both a mediator and moderator in the link between work ethics and employee performance, and also reinforces empirical data regarding the relevance of work motivation theory in organizational settings.